2013
DOI: 10.1016/j.ijmm.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Infection prevention in a connected world: The case for a regional approach

Abstract: Results from microbiological and epidemiological investigations, as well as mathematical modelling, show that the transmission dynamics of nosocomial pathogens, especially of multiple antibiotic-resistant bacteria, is not exclusively amenable to single-hospital infection prevention measures. Crucially, their extent of spread depends on the structure of an underlying "healthcare network", as determined by inter-institutional referrals of patients. The current trend towards centralized healthcare systems favours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 48 publications
1
63
0
Order By: Relevance
“…This entails close collaboration of all health-care facilities (i.e. hospitals, but also general practices and long-term care facilities) within a clearly defined region [18]. Harmonization of guidelines and practices can be a first start regarding this aspect [19].…”
Section: Importance Of a Broad Stewardship Programmentioning
confidence: 99%
“…This entails close collaboration of all health-care facilities (i.e. hospitals, but also general practices and long-term care facilities) within a clearly defined region [18]. Harmonization of guidelines and practices can be a first start regarding this aspect [19].…”
Section: Importance Of a Broad Stewardship Programmentioning
confidence: 99%
“…In addition, it has already been demonstrated that patient transfers between hospitals significantly increase the transmission of hospital-acquired infections at the regional and national scale [11]. …”
Section: Introductionmentioning
confidence: 99%
“…The implementation of harmonised preventive standards in the regional healthcare cluster, where the nosocomial pathogen spreads predominantly is more likely to be successful. The hospitals of the Dutch-German border region EUREGIO have been confirmed to represent such a regional healthcare cluster using mathematical modelling [14]. Therefore, the governments of the 16 German Bundesländer (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…To reinforce regional cooperation and overcome the problem of limited local implementation, all 40 hospitals in the Münsterland region in NRW are cooperating in the EU-funded Dutch-German EUREGIO MRSA-net (www.mrsa-net.eu) and EurSafety HealthNet (www.eursafety.eu) projects since 2005. Since these 40 hospitals form a connected healthcare cluster [14], and contain all hospitals in the region, they can be considered to form a single patient catchment area.…”
Section: Introductionmentioning
confidence: 99%